Violence Breeds Violence: Childhood Exposure and Adolescent Conduct Problems - Weaver, Chelsea M. (2008)
The relationships between childhood exposure to violence and adolescent conduct problems were investigated in a sample of 88 primiparous adolescent mothers and their children. Regression analyses revealed that witnessing violence and victimization prior to age 10 predicted delinquency and violent behaviors, even after controlling for prenatal maternal and early childhood externalizing problems. Social competency and depression during middle childhood moderated the relationship between victimization and violent behaviors for girls, but not boys: Lower levels of social competency and depression served as risk factors for delinquency among teenage girls who experienced victimization during childhood. These findings have important implications for youth violence prevention programs.